Komunikasi Efektif Orang Tua dalam Mengenali Bahasa Cinta Anak Usia Dini - Sari, Novita; Harlina, Harlina; Cahyati, Deti; Nadivah, Nadivah; Fitriani, Nur; Chamsanah, Chamsanah; Rohmatiah, Siti; Kartini, Kartini; Purwamiluyah, Purwamiluyah; Handawiyah, Robiatul (Universitas Pahlawan Tuanku Tambusai, 2026)
The Community Partnership Program (PKM) aims to improve parents' understanding of the importance of effective communication in recognizing and adjusting the love language of early childhood. Love language is a child's way of receiving and expressing affection, which consists of five main forms: physical touch, words of affirmation, quality time, acts of service, and giving gifts. Through socialization, interactive discussions, and practical simulations, participants gain new insights into communication strategies that are appropriate to children's emotional needs. This activity was carried out at KB Ummatan Washaton, while the community-based research method was used in community service with a qualitative approach. The form of community service activities was carried out using the FGD (Focus Group Discussion) approach, Literature Review, and socialization. The results of the activity showed that many parents who initially did not understand the concept of love language, are now more aware of the importance of adjusting their communication patterns to be more effective in building emotional closeness with their children. However, the challenge of changing old habits is still an obstacle, so further assistance is needed so that the implementation of this concept runs consistently. Overall, this PKM has a positive impact on improving parents' communication skills, which are expected to support children's social and emotional development optimally.